2010
DOI: 10.1016/j.ecss.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Complex vertical migration of larvae of the ghost shrimp, Nihonotrypaea harmandi, in inner shelf waters of western Kyushu, Japan

Abstract: The position of meroplanktonic larvae in the water column with depth-dependent current velocities determines horizontal transport trajectories. For those larvae occurring in inner shelf waters, little is known about how combined diel and tidally-synchronized vertical migration patterns shift ontogenetically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 27 publications
1
72
0
Order By: Relevance
“…Puls (2002) found that first zoeae of N. californiensis were more abundant in surface than in bottom waters during nocturnal ebb tides in the South Slough estuary, Oregon, whereas Pimentel (1983) found that they were uniformly distributed across depths over both tidal phases. Other Callianassids have been found to perform tidal migrations, e.g., Nihonotrypaea harmandi on the inner shelf of western Kyushu, Japan (Tamaki et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Puls (2002) found that first zoeae of N. californiensis were more abundant in surface than in bottom waters during nocturnal ebb tides in the South Slough estuary, Oregon, whereas Pimentel (1983) found that they were uniformly distributed across depths over both tidal phases. Other Callianassids have been found to perform tidal migrations, e.g., Nihonotrypaea harmandi on the inner shelf of western Kyushu, Japan (Tamaki et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Larval bi valves are thought to respond to lunar cues, which are generally linked to light intensity and/or a combination of tidal and diel cues (Manuel & O'Dor 1997). Older larvae of bivalves and decapods tend to be more abundant near the seafloor than younger ones, presumably due to an increase in specific gravity and change in morphology or behaviour (Brookins & Epifanio 1985, Tamaki et al 2010. Near-bottom distribution presumably enhances the probability of locating a suitable site for settlement.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…In the field and laboratory, the vertical distribution of planktotrophic larvae is often related to the presence of food patches (Raby et al 1994, Metaxas & Young 1998, Sa meoto & Metaxas 2008b). Both bryozoan and caridean larvae have the chemosensory ability to detect food (Kingsford et al 2002), and laboratory observations have shown direc ted movement towards food supply for the decapod, Nihonotrypaea harmandi (Tamaki et al 2010). Once within the food patch (i.e.…”
Section: Spatial and Temporal Patterns In Vertical Distributionmentioning
confidence: 99%
“…Larval distributions of near-shore marine invertebrates appear to be adapted for remaining in local circulation cells even in strong upwelling areas (Morgan et al 2009) and, not surprisingly, for returning to source populations and habitats (Wooldridge and Loubser 1996;Shanks and Roegner 2007). Behavioral adaptations for restricted larval dispersal are common among decapods, including thalassinid shrimp (Tamaki et al 2010, Wooldridge and Loubser 1996, Queiroga and Blanton 2005. The lack of mud shrimp host species in the Siberian Western Pacific Ocean (Williams 1986) also precludes O. griffenis dispersal across the North Pacific by island hopping through host populations.…”
Section: Natural Transoceanic Dispersal On Ocean Currentsmentioning
confidence: 96%